Человек, общество и абсолют как субъекты права - Ивакин, Алексей Аркадьевич; Івакін, Олексій Аркадійович; Ivakin, Aleksej (My University, 2012)
Basing on empirical facts and conclusions of philosophy, science and religion, the author tries to prove that a man, who, as it usually seems, is the only subject of law, in fact, is the dialectical unity of the three subjects of law — the individual, the society and the Absolute. In this connection, free and creative nature of man, whose implementation as the free will is carried out in legal space, has not only individual and social, but also cosmic, divine dimension.
Ивакин А. А. Человек, общество и абсолют как субъекты права / А. А. Ивакин // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. - Вип. 67. - С. 106-112.
Keywords: право; воля; субъект; абсолют; человек; общество; мораль; нравственность; ноосфера; суб’єкт; людина; суспільство; моральність; law; will; subject; absolute; people; society; morality; ethics; noosphere